Mindfulness fills in the blank spaces left by affective uncertainty uplifting adaptive behaviors - Junça Silva, A.; Caetano, A. (The Spanish Journal of Psychology, 2023)
Drawing on the integrative model of uncertainty tolerance, we aimed to investigate whether uncertainty relates to adaptive performance, at the within-person level. We argue that daily uncertainty at work will trigger negative affective reactions that, in turn, will minimize adaptive performance. Moreover, we focus on socio-cognitive mindfulness as a cross-level moderator of the indirect relationship of uncertainty on adaptive performance via negative affect. To capture changes in daily life and test our model, we conducted two diary studies across 5-working days: One with a sample of telecommuters (n = 101*5 = 505), and the other with a sample of non-telecommuters (n = 253*5 = 1,265). Study 1 took place between February and March of 2021 (during the mandatory confinement), and Study 2 occurred between April and May 2021 (out of the mandatory confinement). Both studies were conducted in Portugal. The multilevel results showed that at the day-level of analysis, uncertainty decreased adaptive performance through the enhanced negative affect. Moreover, at the person-level of analysis mindfulness moderated (a) the direct relationship of uncertainty to adaptive performance, and (b) the indirect relationship of uncertainty to adaptive performance via negative affect, in such a way that it became weaker when mindfulness was higher (multilevel-mediated moderation effect). This relation was different between Studies 1 and 2; that is, in Study 1, teleworkers who were high on mindfulness engaged in more adaptive performance when negative affect was high. In Study 2, adaptive performance significantly decreased, when negative affect was higher, even though this effect was weaker for mindful of individuals. The findings show that mindfulness helps to fill in the spaces of the affective uncertainty attenuating its detrimental effects.